The Effect of Firm Size and Sales Growth on Profitability Mediated by Capital Structure - Nekky Rahmiyati; Listiana Sri Mulatsih; Alfiana Alfiana; Puji Afriyeni; Teguh Setiawan Wibowo (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
The purpose of this study was to determine the effect of firm size and sales growth on profitability mediated by capital structure. The object of this research is a manufacturing company in the consumer goods industry sub-sector on the IDX 2018-2022. This research occurred because there was a phenomenon of increasing and decreasing profitability that occurred in several consumer good industry companies on the IDX during the 5 year period. This type of research is quantitative research, sampling using purposive sampling method that meets the criteria. This study uses secondary data obtained from the IDX. The research results show that firm size, sales growth, and capital structure have a positive effect on profitability.